Hypothesis-free secretome analysis of thoracic aortic aneurysm reinforces the central role of TGF-β cascade in patients with bicuspid aortic valve. Issue 3 (March 2017) - Rocchiccioli, Silvia; Cecchettini, Antonella; Panesi, Paola; Farneti, Pier Andrea; Mariani, Massimiliano; Ucciferri, Nadia; Citti, Lorenzo; Andreassi, Maria Grazia; Foffa, Ilenia
Abstract: Background: Ascending thoracic aortic aneurysm (ATAA) is a major cause of morbidity and mortality worldwide. The pathogenesis of medial degeneration of the aorta remains undefined. High-throughput secretome analysis by mass spectrometry may be useful to elucidate the molecular mechanisms involved in aneurysm formation as well as to identify biomarkers for early diagnosis or targets of therapy. The purpose of the present study was to analyze the secreted/released proteins from ATAA specimens of both tricuspid aortic valve (TAV) and bicuspid aortic valve (BAV) patients. Methods: Aortic specimens were collected from patients undergoing elective surgery and requiring graft replacement of the ascending aorta. Each sample of the ascending aortic aneurysm, 4 BAV (3 males; aged 53.5 ± 11.4 years) and 4 TAV (1 male; 78 ± 7.5 years), was incubated for 24 h in serum-free medium. Released proteins were digested with trypsin. Peptide mixtures were fractioned by nano-high performance liquid chromatography and analyzed by mass spectrometry. Following identification of differentially expressed proteins, quantitative real time polymerase chain reaction (qRT-PCR) analysis was performed. Results: The comparison between the proteins released from BAV and TAV aneurysmatic tissues showed significantly diverging expression fingerprints in the two groups of patients. Bioinformatics analysis revealed 38 differentially released proteins; in particular 7 proteins were down-regulated while 31 were up-regulated in BAV with respect to TAV. Most of the proteins that were up-released in BAV were related to the activation of transforming growth factor (TGF)-β signaling. Latent TGF-β binding protein 4 (LTBP4) exhibited one of the highest significant under-expressions (10-fold change) in BAV secretomes with respect to TAV. qRT-PCR analysis validated this significant difference at LTBP4 gene level (BAV: 1.03 ± 0.9 vs TAV: 3.6 ± 3.2; p < 0.05). Conclusion: Hypothesis-free secretome profiling clearly showed diverging expression fingerprints in the ATAA of TAV and BAV patients, confirming the crucial role of TGF-β signaling in modulating ATAA development in bicuspid patients.